Interaction Interface of Mason-Pfizer Monkey Virus Matrix and Envelope Proteins - Prchal, Jan; Sýs, Jakub; Junková, Petra; Lipov, Jan; Ruml, Tomáš (Journal of virology, 2020)
Retroviral envelope glycoprotein (Env) is essential for the specific recognition of the host cell and the initial phase of infection. As reported for human immunodeficiency virus (HIV), the recruitment of Env into a retroviral membrane envelope is mediated through its interaction with a Gag polyprotein precursor of structural proteins. This interaction, occurring between the matrix domain (MA) of Gag and the cytoplasmic tail (CT) of the transmembrane domain of Env, takes place at the host cell plasma membrane. To determine whether the MA of Mason-Pfizer monkey virus (M-PMV) also interacts directly with the CT of Env, we mimicked the in vivo conditions in an in vitro experiment by using a CT in its physiological trimeric conformation mediated by the trimerization motif of the GCN4 yeast transcription factor. The MA protein was used at the concentration shifting the equilibrium to its trimeric form. The direct interaction between MA and CT was confirmed by a pulldown assay. Through the combination of nuclear magnetic resonance (NMR) spectroscopy and protein cross-linking followed by mass spectrometry analysis, the residues involved in mutual interactions were determined. NMR has shown that the C terminus of the CT is bound to the C-terminal part of MA. In addition, protein cross-linking confirmed the close proximity of the N-terminal part of CT and the N terminus of MA, which is enabled in vivo by their location at the membrane. These results are in agreement with the previously determined orientation of MA on the membrane and support the already observed mechanisms of M-PMV virus-like particle transport and budding.IMPORTANCE By a combination of nuclear magnetic resonance (NMR) and mass spectroscopy of cross-linked peptides, we show that in contrast to human immunodeficiency virus type 1 (HIV-1), the C-terminal residues of the unstructured cytoplasmic tail of Mason-Pfizer monkey virus (M-PMV) Env interact with the matrix domain (MA). Based on biochemical data and molecular modeling, we propose that individual cytoplasmic tail (CT) monomers of a trimeric complex bind MA molecules belonging to different neighboring trimers, which may stabilize the MA orientation at the membrane by the formation of a membrane-bound net of interlinked Gag and CT trimers. This also corresponds with the concept that the membrane-bound MA of Gag recruits Env through interaction with the full-length CT, while CT truncation during maturation attenuates the interaction to facilitate uncoating. We propose a model suggesting different arrangements of MA-CT complexes between a D-type and C-type retroviruses with short and long CTs, respectively.
Keywords: Env; protein interactions; proteinové domény; Masonův-Pfizerův opičí virus; Gene Products, gag; Mason-Pfizer monkey virus; genové produkty gag; cytoplasmic tail; Retrovirus; Protein Domains; Gene Products, env; M-PMV; genové produkty env